2008
DOI: 10.1021/bi800026k
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Clinical Lethality of Osteogenesis Imperfecta from Collagen Glycine Mutations

Abstract: Osteogenesis imperfecta (OI), or brittle bone disease, often results from missense mutation of one of the conserved glycine residues present in the repeating Gly-X-Y sequence characterizing the triplehelical region of type I collagen. A composite model was developed for predicting the clinical lethality resulting from glycine mutations in the R1 chain of type I collagen. The lethality of mutations in which bulky amino acids are substituted for glycine is predicted by their position relative to the N-terminal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
73
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 32 publications
9
73
0
Order By: Relevance
“…A recent computational study has focused on the asymmetric influence of tripeptides flanking a Gly to Ser mutation site, noting that a destabilizing triplet C-terminal to a Gly to Ser substitution is correlated with a lethal OI phenotype, whereas no correlation is seen for an N-terminal destabilizing triplet (11). Consistent with this result, peptide studies showed a greater destabilization effect when a tripeptide of low triple helix propensity is put on the C-terminal side when compared with the N-terminal side of a Gly to Ser substitution (11).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent computational study has focused on the asymmetric influence of tripeptides flanking a Gly to Ser mutation site, noting that a destabilizing triplet C-terminal to a Gly to Ser substitution is correlated with a lethal OI phenotype, whereas no correlation is seen for an N-terminal destabilizing triplet (11). Consistent with this result, peptide studies showed a greater destabilization effect when a tripeptide of low triple helix propensity is put on the C-terminal side when compared with the N-terminal side of a Gly to Ser substitution (11).…”
Section: Discussionmentioning
confidence: 99%
“…A recent computational study has focused on the asymmetric influence of tripeptides flanking a Gly to Ser mutation site, noting that a destabilizing triplet C-terminal to a Gly to Ser substitution is correlated with a lethal OI phenotype, whereas no correlation is seen for an N-terminal destabilizing triplet (11). Consistent with this result, peptide studies showed a greater destabilization effect when a tripeptide of low triple helix propensity is put on the C-terminal side when compared with the N-terminal side of a Gly to Ser substitution (11). The NMR dynamic studies presented here on the T1-898(G901S) peptide suggest an inherent asymmetry surrounding a mutation site with less regular hydrogen bonding or increased conformational flexibility on the C-terminal side, and this inherent effect could be synergistic with the sequence-dependent stability of neighboring triplets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The database has been used in the development of a model for predicting clinical lethality of mutations resulting in replacement of glycine with serine in type I collagen, which provided insight into the etiology of osteogenesis imperfecta [Bodian et al, 2008]. Analysis of the collected data also revealed that most Arg-Cys substitutions within the triple helical domains of the chains of type I collagen are colocated in a narrow region of the fibril overlapping band ''e'' in the gap zone (unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleotide data are provided as custom tracks for display in the UCSC genome browser [Kent et al, 2002], which permits viewing of the collagen-specific information in the context of the wealth of genomic data available through this popular tool. Analysis of the integrated data can lead to insights into the function of native collagen molecules and the mechanisms by which sequence variations lead to disease [Bodian et al, 2008].…”
Section: Introductionmentioning
confidence: 99%